Effects of Dietary Inclusion of Dry Hydrastis canadensis on Laying Performance, Egg Quality, Serum Biochemical Parameters and Cecal Microbiota in Laying Hens - Tzeng, Tzuen-Rong J (Animals (Basel), 2021)
SIMPLE SUMMARY: Extensive studies on alternative sources of feed additives to replace antibiotics are required. Plants of the Ranunculaceae family have been used as medicines or dyes. The representative plant is goldenseal (Hydrastis canadensis), which has a long history of use in North America, with berberine considered the most effective ingredient in goldenseal. Some natural compounds in Hydrastis canadensis function as efflux pump inhibitors and thus may have bactericidal effects against pathogens with antibiotic resistance. However, no conclusive beneficial effects of goldenseal on the livestock industry have been reported. The objective of this study was to examine whether the alternative use of goldenseal roots or leaves has potential health benefits in chickens. Our data demonstrate that Hydrastis canadensis can improve the egg quality and modulate the microbiota composition of laying hens. ABSTRACT: Alternative growth promoters are able to not only effectively replace the traditional use of antibiotics but also provide additional health benefits for livestock and reduce food safety concerns. This study investigated the effects of dry Hydrastis canadensis on the laying performance and fecal microbial community of laying hens. Twenty-four Lohmann (LSL, white layer strain) hens were reared from 40 to 48 weeks of age and randomly allotted to four dietary treatments (six birds/treatment). The dietary treatments comprised a basal diet with no treatment as control, a basal diet plus 0.6% powder of dry Hydrastis canadensis roots (R) or leaves (L), and a basal diet plus 0.6% powder of a mixture of dry Hydrastis canadensis roots and leaves (1:1, LR). No mortality was observed in the whole experimental period. The results indicated that albumen height in the LR group was significantly greater than that in the control group. The diet supplemented with Hydrastis canadensis had no significant effects on egg production rate, egg weight, eggshell strength, eggshell thickness, Haugh unit, or yolk height during the whole experimental phase. However, principal coordinate analysis, comparative heat map analysis, and cluster dendrogram analysis of cecal microbiota showed distinct clusters among the groups treated with Hydrastis canadensis and the control group. Regarding blood biochemical parameters, serum cholesterol levels were significantly lower in all Hydrastis canadensis-treated groups compared with those in the control group. Moreover, serum low-density lipoprotein levels were lower in hens supplemented with the leaf of Hydrastis canadensis. The abundances of the phyla Fusobacteria and Kiritimatiellaeota were increased (p < 0.05) in laying hens fed with 0.6% Hydrastis canadensis leaves, whereas the abundance of the phylum Firmicutes in cecum digesta decreased in response to treatment with Hydrastis canadensis roots and leaves. The relative abundance of the Fusobacterium genus was higher in the LR group compared with that in the control. On the contrary, we found a different trend in the Synergistes genus. The potential influences of these microbiota on the performance of laying hens were discussed. The results demonstrate that Hydrastis canadensis can improve the egg albumen height and modulate the cecum digesta microbiota composition of laying hens.